Expediting Court Dispositions: Quick Results, Uncertain Outcomes - Taxman, Faye S. (Journal of research in crime and delinquency, 1999)
Surging criminal court dockets have fostered an interest in differentiated case management and specialized dockets to expedite the processing of criminal cases. An experiment was conducted on a modified differentiated case management process to determine the impact of the review and screening on case outcomes (e.g., type of case disposition and type of sentence) and system outcomes (e.g., amount of bed space consumed during pretrial and sentenced periods). Overall, this research confirms that an early screening process has many benefits by reducing the average length of time for court disposition, length of time for pretrial incarceration, and the average sentence length for cases. A possible drawback of the process is the potential for net widening. Results from the experiment are also useful in providing new insights into the eligibility and impact of such processes